Nuclear response to dark matter signals in Ge and Xe odd-mass targets - Sáez, María Manuela (2023)
The interaction of dark matter particles (WIMPs) with the odd-mass 73 Ge and131 Xe target nuclei is analyzed, in the context of the minimal extensions of the SUSYmodel. The BCS+QRPA technique plus the quasiparticle-phonon coupling scheme isused to describe the nuclear structure part of the calculations. The resulting values forthe nuclear spin content of both nuclei are compared with values previously reported inthe literature.